Holographic CFTs on AdS d × S n and conformal defects - Ahmad Ghodsi; Elias Kiritsis; Francesco Nitti (Journal of High Energy Physics, 2023)
Abstract We consider (d+n+1)-dimensional solutions of Einstein gravity with constant negative curvature. Regular solutions of this type are expected to be dual to the ground states of (d + n)-dimensional holographic CFTs on AdS d × S n . Their only dimensionless parameter is the ratio of radii of curvatures of AdS d and S n . The same solutions may also be dual to (d − 1)-dimensional conformal defects in holographic QFT d+n . We solve the gravity equations with an associated conifold ansatz, and we classify all solutions both singular and regular by a combination of analytical and numerical techniques. There are no solutions, regular or singular, with two boundaries along the holographic direction. Out of the infinite class of regular solutions, only one is diffeomorphic to AdS d+n+1 and another to AdS d × AdS n+1. For the regular solutions, we compute the on-shell action as a function of the relevant parameters.